IEEE International Symposium on High-Performance Comp Architecture 2012
DOI: 10.1109/hpca.2012.6169031
|View full text |Cite
|
Sign up to set email alerts
|

Computational sprinting

Abstract: Although transistor density continues to increase, voltage scaling has stalled and thus power density is increasing each technology generation. Particularly in mobile devices, which have limited cooling options, these trends lead to a utilization wall in which sustained chip performance is limited primarily by power rather than area. However, many mobile applications do not demand sustained performance; rather they comprise short bursts of computation in response to sporadic user activity.To improve responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(90 citation statements)
references
References 39 publications
(44 reference statements)
1
87
1
1
Order By: Relevance
“…Perhaps counter-intuitively, however, we find sprinting can actually result in net gains in energy efficiency by (i) amortizing the fixed uncore power consumption over a larger number of active cores and (ii) capturing race-to-idle effects. Our conclusions stand in contrast to our previously published predictions from simulation-based analysis of computational sprinting [45], which neglected uncore power and hence suggested that sprinting might at best be energy neutral.…”
Section: Energy Impacts Of Sprintingcontrasting
confidence: 56%
See 2 more Smart Citations
“…Perhaps counter-intuitively, however, we find sprinting can actually result in net gains in energy efficiency by (i) amortizing the fixed uncore power consumption over a larger number of active cores and (ii) capturing race-to-idle effects. Our conclusions stand in contrast to our previously published predictions from simulation-based analysis of computational sprinting [45], which neglected uncore power and hence suggested that sprinting might at best be energy neutral.…”
Section: Energy Impacts Of Sprintingcontrasting
confidence: 56%
“…A complementary approach to increase sprinting effectiveness is to engineer a system that supports longer sprints by including more thermal capacitance. Instead of leveraging only the specific heat of conventional materials, prior work proposed using the latent heat of a phase change material (PCM) to add thermal capacitance to a sprinting system [45]. Latent heat has the advantage that it can absorb substantial heat without a change in temperature.…”
Section: Extending Sprints Using Latent Heatmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis makes sense for some workloads and tasks, for example, the image recognition kernel in [13], and perhaps the UI controls on the platform (Section VI-E), but it may not capture the event-driven nature of JavaScript execution for a web page or application. Here, the workload is likely to be continuous, and in many cases, users may not be concerned with the speed at which individual tasks complete, or even if they complete.…”
Section: Introductionmentioning
confidence: 99%
“…The implication is that given fixed tasks, the best strategy is to execute them with as high a rate as possible. Computational sprinting [13], where execution rate is raised even beyond sustainable thermal limits for brief periods of time, is the extreme example of this "race to finish" approach.…”
Section: Introductionmentioning
confidence: 99%